2022
DOI: 10.1039/d1sm01585k
|View full text |Cite
|
Sign up to set email alerts
|

Chiral columns forming a lattice with a giant unit cell

Abstract: Mesogenic materials, quinoxaline derivatives with semi-flexible cores, are reported to form new type of 3D columnar structure with large crystallographic unit cell and Fddd lattice below columnar hexagonal phase. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
1
8
1
Order By: Relevance
“…The appearance of the highly ordered yet noncrystalline Fddd phase confirmed that the chirality of close-packed twisted ridged (i.e., noncircular) columns, without any junctions, can indeed be maintained over a long range. Subsequently, the Fddd phase was also found in a compound with an -shape core, one-ring wide in the middle and two-ring wide at each end . Our preliminary studies also suggest that this phase and its variants may be widespread in polycatenars, including those formed by hydrogen-bonded half-rods and in side-chain LC polymers.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…The appearance of the highly ordered yet noncrystalline Fddd phase confirmed that the chirality of close-packed twisted ridged (i.e., noncircular) columns, without any junctions, can indeed be maintained over a long range. Subsequently, the Fddd phase was also found in a compound with an -shape core, one-ring wide in the middle and two-ring wide at each end . Our preliminary studies also suggest that this phase and its variants may be widespread in polycatenars, including those formed by hydrogen-bonded half-rods and in side-chain LC polymers.…”
Section: Introductionsupporting
confidence: 56%
“…Subsequently, the Fddd phase was also found in a compound with an I-shape core, one-ring wide in the middle and two-ring wide at each end. 44 Our preliminary studies also suggest that this phase and its variants may be widespread in polycatenars, including those formed by hydrogen-bonded half-rods and in side-chain LC polymers. It would also not be surprising if it was found in compounds with 3-arm star molecules of C 3 symmetry that also form a columnar phase at higher temperatures.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…[ 25 ] Recently, Rybak et al reported quinoxaline derivatives with semiflexible cores stabilizing Col mesomorphism. [ 36 ] All the above said works motivated us to try the new possibility of combining carbazole units with pyrazino[2,3‐g]quinoxaline central core.…”
Section: Introductionmentioning
confidence: 99%